Application of hyperthermic intraperitoneal chemotherapy at the University Clinical Center of Republic of Srpska - Zoran G. Aleksić; Dragan Tomić; Velimir Škrbić; Nenad Jaćimović; Miroslav Popović; Sladibor Lakić (Биомедицинска истраживања, 2025)
Introduction: Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is an advanced treatment modality for peritoneal malignancies, including ovarian cancer, appendix adenocarcinoma, colorectal cancer, and peritoneal metastases. This approach offers potential benefits in managing these complex conditions. Methods: The effectiveness of CRS with HIPEC depends on the selection of cytostatics, their pharmacokinetics, and pharmacodynamics. Although these complex surgical procedures are associated with certain risks, they typically result in fewer complications and shorter hospital stays. Results: The first CRS-HIPEC procedure at the University Clinical Center of Republic of Srpska was conducted on February 26, 2020. From February 2020 to February 2023, 42 CRS-HIPEC procedures were performed with favorable postoperative outcomes. The treatment led to a lower incidence of intraoperative (0%) and postoperative complications (11.9% in five patients), reduced side effects of local chemotherapy compared to systemic chemotherapy, and a decrease in mortality rates (2.4% in one patient). The patients were aged between 40 and 70 years. A multidisciplinary team of surgeons, gynecologists, anesthesiologists, oncologists, and perfusionists carried out the procedures. Conclusion: Local intraoperative chemotherapy through HIPEC represents a modern and effective treatment approach that improves both surgical and oncological outcomes. Our institution and the Clinic for General and Abdominal Surgery should continue to adopt innovative procedures to enhance treatment and patient care.
Keywords: hyperthermic intraperitoneal chemotherapy (HIPEC); cytoreductive surgery (CRS); ovarian cancer; peritoneal metastases (PC)